AnalisisPengaruh FraudPentagonUntukMendeteksi Manipulasi Laporan Keuangan - Garin Puspitasari; Ambar Woro Hastuti (Jurnal Akuntansi dan Perpajakan, 2020)
This research is to find out the influence of fraud pentagon for detection fraudulent financial reporting. Fraud Pentagon as independent variable which has five elements, namely: (1) Pressure, which proxied by financial stability, external pressure, and good corporate governance; (2) Opportunity, proxied with ineffective monitoring; (3) Rationalization, which proxied by change in auditors; (4) Competence, proxied with change of directors; (5) Arrogance, which proxied by political connection. Whereas for dependent variable is fraudulent financial reporting as measured by fraud score model(F-Score). The sample of this research are 21 State-Owned Enterprises (BUMN) who reported annual report on the company’s website period 2013-2017. This research use multiple linear regression method with 23 SPSS Software. This research shows that financial stability, external pressure, and change in auditor are significant in detecting fraudulent financial reporting. These variabel represent two elements in fraud pentagon, namely pressure and rationalization. And than good corporate governance, ineffective monitoring, change of directors, and political connection are not significant in detecting fraudulent financial reporting. DOI: 10.26905/ap.v6i1.4007